Universal passivation strategy to slot-die printed SnO2 for hysteresis-free efficient flexible perovskite solar module - Tongle Bu (Nature Portfolio, 2018)
Uniformity and hysteresis are long lasting problems for flexible perovskite solar modules. Here Bu et al. develop a universal potassium passivation strategy to improve the quality of slot-die printed tin oxide electron transport layers and demonstrate highly efficient and hysteresis-free flexible devices.